Hubungan Keanekaragaman Makrobentos dengan Habitat Ikan di Sungai pada Ekowisata Berbeda - Umi Nurjanah; Haqqi Anajili Setiyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the relationship between macrobenthos diversity and fish habitat through biotic and abiotic parameters and provide an overview of the impact of ecotourism on the health of river ecosystems. The methods used include field surveys, macrobenthos sampling using the kicking method, measuring physical and chemical parameters of the water, and statistical analysis. The results obtained are that Kampung Durian tourism has the highest macrobenthos diversity index with an index value of 2.476. The results of the ANOVA analysis showed a significance value of 0.529, which means there is no significant effect between the three levels of ecotourism on the macrobenthos diversity index. The relationship between macrobenthos diversity and fish habitat, namely water chemistry-physics based on regression analysis, has a significant relationship of 0.03. The relationship between temperature and macrobenthos diversity is negative, while pH and DO are positive. The conclusion is that macrobenthos diversity and fish habitat have a significant relationship but there is no significant effect from different levels of ecotourism intensity. Keywords: Ecotourism, Fish Habitat, Macrobenthos